Lawsone encapsulated polylactic‐co‐glycolic acid nanoparticles modified with chitosan‐folic acid successfully inhibited cell growth and triggered apoptosis in Panc‐1 cancer cells - Helia Ghafaripour; Masoud Homayouni Tabrizi; Ehsan Karimi; Niloofar Barati Naeeni (IET Nanobiotechnology)
Abstract The present research aims to encapsulate lawsone in polylactic‐co‐glycolic acid (PLGA) nanoparticles modified with folic acid (FA) and chitosan (CS) to study its anticancer effects against Panc‐1 cells. The nanoparticles were analysed in means of shape/size and zeta potential index using scanning electron microscope and dynamic light scattering. High‐performance liquid chromatography was applied to evaluate the lawsone entrapment efficacy. The authors performed acridine orange/propidium iodide staining and flow cytometry to monitor apoptosis induction and cell cycle arrest. The expressions of apoptosis‐related genes (BAX and BCL‐2) were assessed by real time PCR. Nanoparticle antioxidative and antibacterial activities were examined by DPPH/ABTS scavenging assay, disk diffusion method, and minimum inhibitory concentration and minimum bactericidal concentration evaluation. The NPs were 229.65 nm, the encapsulation efficiency was 81%. The concentration of lawsone that exerts 50% cell growth inhibition (IC50) against Panc‐1 cells was calculated 118.4 μL. Apoptosis induction was evidenced by the increased number of orange cells and increased proportion of cells in G1‐Sub phase respectively. Moreover, lawsone‐loaded nanoparticle upregulated BAX gene expression, while downregulated BCL2expression, suggesting the activation of apoptotic pathway. The observed cytotoxic/apoptotic properties suggest that Lawson‐loaded PLGA‐FA‐CS‐NPs hold a great potential in pancreatic cancer treatment.